Islamic Fintech Financing Adoption Amongst Asnaf Micro Entrepreneurs in Malaysia: Extended UTAUT2 - Farah Farhana Jauhari; Syarah Syahira Mohd Yusoff; Salina Hj Kassim (Bank Indonesia, 2025)
Zakat serves as a significant mechanism for improving Asnaf’s income. Participants in the Islamic financial industry have acknowledged its potential and adopted various fintech strategies, per Bank Negara Malaysia's support for a more proactive collaborative approach to enhance Malaysia's Islamic social finance (ISF) landscape. Statistics and reports about technology adoption among Asnaf are scarce. This study examines how the extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and Technology-Organisation-Environment (TOE) factors affect Asnaf micro entrepreneurs in Malaysia's use of Islamic fintech financing. Following a thorough data screening process, a total of 292 samples is accepted for analysis using a partial least squares structural equation model (PLS-SEM). Performance expectancy, price value, shariah financial literacy, perceived trust, and consumer pressure all significantly and positively influence the intention to use Islamic fintech financing. Subsequently, adoption is significantly influenced by behavioural intentions and facilitating conditions. This research represents one of the initial investigations into end users' factors influencing the adoption of Islamic fintech among Asnaf micro entrepreneurs, a field that is still nascent.